Profil Perkembangan Multidomain Anak Slow Learner - Aliyatul Ulya; Ira Darmawanti (CV. ITTC INDONESIA, 2026)
Children classified as slow learners-with IQ scores from 70-89 require comprehensive, multi-domain developmental assessment and intervention. This qualitative single-case study describes the cognitive-perceptual, social-emotional, and affective-motivational development profiles of a 12-year-old male subject (A) receiving individualized special needs children’s facility. Data were gathered through five structured observation sessions, semi-structured alloanamnesis interviews with parents and a mentor teacher, one home-visit observation, and autoanamnesis session with the subject. Thematic analysis following the Miles and Huberman model was applied. Findings reveal that subject (A) demonstrates academic competencies consistent with early concrete-operational functioning-below chronological expectations-including difficulties in alphabetic sequencing, reading closed-syllable words (KV-KVK patterns), and tens-place numeracy. Socially, the subject withdraws in unfamiliar settings and avoids peer interaction due to pervasive low self-confidence. Affectively, passive learning behaviors, complete dependence on external validation, and low intrinsic motivation dominate. These findings are interpreted through Piaget’s (1952) cognitive development theory, Bandura’s (1997) social learning and self-efficacy framework, and Erikson’s (1963) Industry vs Inferiority stage. Environmental contributors including prenatal stress exposure, inconsistent parental engagement with the intervention program, and an absence of early motor therapy-are identified as significant moderators. Targeted stimulation programs encompassing cognitive scaffolding, social-emotional competency building,, and systematic positive reinforcement are proposed.